GIS-based flood risk zoning of the Khando river basin in the Terai region of east Nepal - Sharma, Keshav P; Adhikari, Naba R; Ghimire, Pawan K; Chapagain, Prem S (Himalayan Journal of Sciences, 2006)
No abstract available. Himalayan Journal of Sciences 1(2): 103-106, 2003